Effect of plasma gas and Ar incorporation on the shear strength between carbon fiber-reinforced thermoplastic polymer and Al - Kim, Yoon Sang; Jung, Unseok; Choi, Sunwoong; Jung, Yong Chae; Lee, Hun-Su; Kim, Jaewoo (ELSEVIER SCI LTD, 2020)
With the growing industrial demand for carbon fiber-reinforced thermoplastic polymers (CFRTPs), there is an urgent need to improve their adhesion to conventional metal substrates. In this study, the effect of plasma gas and Ar incorporation on the shear strength between CFRTP and Al was examined. Although NH3 plasma had a greater effect on the surface properties of CFRTP than O-2 plasma, the incorporation of Ar into O-2 plasma showed a 280% improvement in shear strength relative to the untreated reference. Plasma treatment proved effective only on the CFRTP surface, with the failure mode switching from adhesive to substrate failure. Spectroscopic analyses revealed that functional groups like C=O, O-C=O, or H2N-C were either newly generated or their quantity increased on the CFRTP surface. Additionally, CFRTP itself acts as an oxygen source, and its shear strength improved significantly under Ar plasma treatment, even without external O-2 supply.
Keywords: MECHANICAL-PROPERTIES; SURFACE-TREATMENT; BONDING STRENGTH; ADHESIVE JOINTS; ALUMINUM; FAILURE; COMPOSITES; PARAMETERS; DAMAGE; FILM